Quality of Life of Adults Before and After Strabismus Surgery at a Tertiary Care Eye Centre of Kathmandu, Nepal - Shrestha, Sabina; Manoranjan, Aparajita; Shrestha, Sushan Man (Medical Journal of Shree Birendra Hospital, 2017)
Introduction: Strabismus affects the quality of life of adults both in functional and psychosocial aspect of life. This study was conducted to compare the health related quality of life in adults before and after strabismus surgery. Methods: It was a prospective quantitative study conducted in Nepal Eye Hospital from Sep 2015 to July 2016. Thirty one adult participants with strabismus undergoing strabismus surgery completed the study. Twenty open ended adult strabismus questionnaire (AS-20) were used to assess the health related quality of life of adults before and one month after strabismus surgery. Results: The overall median score of adult strabismus questionnaire for quality of life improved from 68.75 (Interquartile range (IQR 25) to 91.25 (IQR 17.5) after strabismus surgery (p value < 0.00). Similarly, the median function subscale and median psychosocial subscale also improved from 72 (IQR 25) to 95 (10) and from 55 (IQR 37.5) to 90 (IQR 15) respectively after surgery. Conclusion: The quality of life of adult strabismic patients improved significantly after stabismus surgery.